DEFINITION AND SCOPE OF POVERTY ECONOMICS AND DEMOGRAPHICS - Isnarini, Eka; Manalu, Rani Wanti; Ramadhani, Salsabilla (LPPM Universitas Bina Bangsa, 2024)
This study aims to identify various factors influencing the socio-economic conditions in Indonesia, with a focus on poverty, urbanization, and their impact on economic development. A variety of relevant literature is used to understand this phenomenon, including studies on urbanization, social inequality and its effects on population growth. Poverty is one of the main focal points, with analysis from several sources as well as the crucial role of education and health in improving human resource quality. This study also examines population control policies and their impact on economic development, as discussed by various authors. The findings from this analysis are expected to provide a better understanding of the challenges faced by Indonesia in reducing socio-economic inequality, as well as offering more effective policy recommendations for achieving sustainable development.